Knowledge, attitudes, and practices toward the treatment of endodontic-periodontal lesions among oral health care providers: a multi-center cross-sectional study - Fei Sun; Mina Hu; Qiuyan Zhu; Jiaqin Wang; Peng Wang; Ying Zhou (BMC Oral Health)
Abstract Background This study aimed to evaluate the knowledge, attitudes, and practices (KAP) of oral healthcare providers concerning the treatment of endodontic-periodontal lesions (EPLs) and investigate the relationships among the KAP dimensions using correlation analysis and structural equation modeling (SEM). Methods This cross-sectional study enrolled dental healthcare professionals between February 2024 and June 2024, with questionnaire data collected in Hangzhou and Shaoxing, China. Data were collected using a self-administered questionnaire that gathered demographic information and KAP scores. Results A total of 281 valid questionnaires were analyzed. Among the participants, 185 (70.08%) were doctors, and 58 (59.85%) had attended relevant academic conferences or training sessions. The mean scores for knowledge, attitude, and practice were 10.06 ± 3.31 (possible range: 0–18), 25.58 ± 2.29 (possible range: 7–35), and 15.70 ± 3.23 (possible range: 5–25), respectively. The SEM revealed that education (β = 0.013, P = 0.013), professional title (β = 0.64, P < 0.001), participation in related research projects (β = -1.84, P < 0.001), and number of patients treated (β = 1.41, P < 0.001) directly influenced knowledge. Knowledge (β = 0.24, P < 0.001) and research participation (β = -0.79, P = 0.026) directly affected attitude. Both knowledge (β = 0.26, P < 0.001) and attitude (β = 0.19, P = 0.023) directly impacted practice. Additionally, education (β = 0.23, P = 0.021), professional title (β = 0.15, P = 0.001), research participation (β = -0.44, P = 0.001), and number of patients treated (β = 0.34, P < 0.001) indirectly influenced attitude, while indirect effects on practice were noted for knowledge (β = 0.04, P = 0.034), education (β = 0.30, P = 0.023), professional title (β = 0.20, P = 0.001), research participation (β = -0.73, P < 0.001), and number of patients treated (β = 0.44, P < 0.001). Conclusions Oral healthcare providers demonstrated limited knowledge, generally positive attitudes, and relatively inactive practices in the treatment of EPLs. To enhance clinical outcomes, targeted educational initiatives and hands-on training should be prioritized to address knowledge gaps and facilitate the translation of positive attitudes into more active and effective clinical practices.